Field-Friendly Test for Monitoring Multiple Immune Response Markers during Onset and Treatment of Exacerbated Immunity in Leprosy - Corstjens, Paul L. A. M. (Clin Vaccine Immunol, 2016)
Acute inflammatory reactions represent the major cause of irreversible neuropathy in leprosy. These tissue-destroying episodes have considerable overlap with acute immunological complications (flares) in several chronic (autoimmune) diseases that similarly warrant early detection. However, the lack of diagnostic tests impedes early diagnosis of these reactions. Here, we evaluated a user-friendly multiplex lateral flow assay for the simultaneous detection of IP-10 and anti-phenolic glycolipid I antibodies for longitudinally monitoring early onset and treatment of leprosy reactions.